Lessons from 11 years of CCAFS: Lessons to support the methane pledge - Wollenberg, Eva Karoline (2022)
"Why agriculture and trade matter in GHG mitigation pathways", presented by Lini Wollenberg for the OECD - Agriculture and Agri-Food Canada Virtual Workshop. From "Mitigating GHG Emissions in Agriculture in an Interconnected World" on April 11-12 2022. This presentation covers the elements of a global strategy, priorities for coordinated action, IPCC, and global food systems emissions. Additional resources listed are the CCAFS AgLED website, Agrochain emissions calculator (ACE), Our World in Data, and FAO emission intensity and food systems data.